Proposal of a minimally invasive technique for acute periapical lesion drainage: A case report and clinical strategy - Magro, Miriam Graziele; Kuga, Milton Carlos [UNESP]; da Costa, Renan Roberto [UNESP]; Venção, Ana Carolina; Vivan, Rodrigo Ricci (Dental Press International, 2016)
Acute periapical lesion is caused by infection of the root canal of the tooth and is characterized by presence of purulent inflammatory exudate in periradicular tissues. It is localized intra and/or extraorally and in some clinical cases there is a need for surgical drainage, which can cause discomfort to the patient. This case report describes a minimally invasive technique for acute periapical lesion drainage using a modified tracheal aspiration probe connected to endodontic aspirators to treat a right maxillary lateral incisor. The technique provides a surgical drainage painless to patient and reduces the risk of spreading infection. After the coronal access of the tooth involved, detoxification and debridement of the root canal, a small incision was performed in palatal mucosa and immediately a modified bronchial aspiration probe was used to aspirate the purulent exudate. In sequence, after remission of the acute signs and symptoms, a surgery with simultaneous root canal filling was performed, using an epoxy-based sealer associated with lateral condensation. The follow-up was for 6 months, through clinical and radiographic analysis and it showed satisfactory bone healing and clinical evolution.
Keywords: Abscess; Cyst; Endodontics; Infection; Surgery